Utility of Regional Anesthesia in Extremity Reconstruction - Weisberger, Joseph S.; Oleck, Nicholas C.; Ayyala, Haripriya S.; Dalena, Margaret M.; Lee, Edward S. (Journal of Reconstructive Microsurgery, 2020)
Background Regional anesthesia (RA) may help to circumvent the well-documented risks associated with general anesthesia, increase patient comfort and satisfaction, and mitigate costs. This study aims to investigate the utility of RA in extremity reconstruction.Methods The American College of Surgeons National Surgical Quality Improvement Program database was queried for all cases of extremity reconstruction including muscle, myocutaneous, or fasciocutaneous flaps from 2005 to 2016. Two groups were created based on anesthesia technique, regional/epidural and general. Postoperative complications included reoperation, readmission, and wound complications. Propensity score matching was utilized to control for variation in sample size, significant comorbidities, and demographics in the analysis of complications.Results A total of 2,874 cases were identified with general anesthesia utilized in 2,820 cases and RA in the remaining 54. After propensity score matching, 53 cases were identified in each group. In both unmatched and matched cohorts, there was no statistically significant difference in the rates of reoperation, readmission, or wound complication rates. In the matched cohort, mean operative time in the RA cohort was significantly shorter, 157.64 (±112.36) minutes compared with 293.06 minutes (±201.35 minutes) in the general anesthesia group (p < 0.001). While no statistically significant difference was detected in mean length of stay (LOS) between the two groups, the RA group experienced a clinically significant shorter LOS of 5.77 days (±5.87 days) compared with 7.02 (±5.61) days in the general anesthesia group (p = 0.269).Conclusion RA may be a safe, reasonable alternative to general anesthesia in extremity reconstruction without increase in postoperative complications. Additionally, RA use is associated with a significant reduction in operative time, potentially leading to shorter and safer procedures without compromising outcomes.
Keywords: anesthesia; extremity; microsurgery; reconstruction